2002
DOI: 10.1046/j.0014-2956.2001.02738.x
|View full text |Cite
|
Sign up to set email alerts
|

In vivo activation of plasma membrane H+‐ATPase hydrolytic activity by complex lipid‐bound unsaturated fatty acids in Ustilago maydis

Abstract: As an adaptation process to the growth retardation provoked by the presence of nonlethal concentrations of ergosterol biosynthesis inhibitors, Ustilago maydis alters the ratio of linoleic to oleic acid bound to plasma membrane complex lipids [Hernández, A., Cooke, D.T., Lewis, M. & Clarkson, D.T. (1997) Microbiology143, 3165–3174]. This alteration increases plasma membrane H+‐ATPase hydrolytic activity. Activation of H+‐ATPase by the linoleic/oleic acid proportion is noncompetitive, nonessential and only invol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 42 publications
0
8
0
Order By: Relevance
“…Similarly Ros et al (1992) and Fodor et al (1995) have indicated that saturation of fatty acid in the membrane of plants growing with metals increased, whereas the level of sterols significantly decreased. Since lipid composition and membrane fluidity are considered as significant factors regulating the plasma membrane H + -ATPase ( Hernandez et al , 2002 ), an inactivation of the proton pump could be the result of the metal-induced changes in the plasma membrane.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly Ros et al (1992) and Fodor et al (1995) have indicated that saturation of fatty acid in the membrane of plants growing with metals increased, whereas the level of sterols significantly decreased. Since lipid composition and membrane fluidity are considered as significant factors regulating the plasma membrane H + -ATPase ( Hernandez et al , 2002 ), an inactivation of the proton pump could be the result of the metal-induced changes in the plasma membrane.…”
Section: Discussionmentioning
confidence: 99%
“…A similar effect was observed in the case of Cu in tomato membrane lipids as a result of 7 days' stress (Ouariti et al, 1997). It is known that PM H + -ATPase is stimulated when the degree of unsaturation of fatty acids is increased (Hernandez et al, 2002). In soybean root, under aluminium stress, up-regulation of transcript, translation and threonine-oriented phosphorylation of plasma membrane H + -ATPase was observed (Shen et al, 2005).…”
Section: Heavy Metalsmentioning
confidence: 92%
“…The activation of H + -ATPase is dependent on the degree of saturation or unsaturation of the fatty acyl chain and its length. The activity decreased with an increase in the length of the fatty acyl chain and in the degree of unsaturation of fatty acid (Hernandez et al, 2002;Kasamo, 2003, Martz et al, 2006. Lysophosphatidylcholine (a natural detergent produced from phosphatidylcholine by phospholipase A 2 ) increased the plasma membrane H + -ATPase activity (Pedechenko et al, 1990, Regenberg et al, 1995.…”
Section: Regulation By Membrane Environmentmentioning
confidence: 99%
“…In potato leaves, the increase in PM H + -ATPase activity could be explained by a simultaneous increase in 18:2 FA in these tissues (Palta and Meade, 1989). A high correlation between PM H + -ATPase activity and 18:3 FA content, or the 18:3/18:2 ratio, was measured in PMs of rye roots (White et al 1990, Hernández et al 2002. In the fungus Ustilago maydis, the 18:2/18:1 ratio is highly correlated with the activation of PM H + -ATPase (Hernández et al 2002).…”
Section: Role Of Fas In the Regulation Of Pm H + -Atpase Activitymentioning
confidence: 99%